The distinctive role of membrane fibrinogen‐like protein 2 in the liver stage of rodent malaria infections. (9th November 2022) - Jiao, Shiming; Tan, Nie; Zhu, Chengyu; Fu, Yong; Zhang, Kun; Ding, Yan; Xu, Wenyue
Abstract: Viral infection often induce the expression of murine fibrinogen‐like protein 2 (mFGL2) triggering immune coagulation, which causes severe liver pathogenesis via increased fibrin deposition and thrombosis in the microvasculature. We aimed to investigate the role of mFGL2 in the liver stage of malaria infections. We reveal that infection with malaria sporozoites also induces increased expression of mFGL2 and that this expression is primarily located within the liver Kupffer and endothelial cells. In addition, we report that inhibition of FGL2 has no significant effect on immune coagulation but increases the expression of inflammatory cytokines in the livers of infected mice. Interestingly, FGL2 deficiency had no significant impact on the development of liver stage malaria parasites or the pathogenesis of the infected liver. In contrast to viral infections, we conclude that mFGL2 does not contribute to either parasite development or liver pathology during these infections, revealing the unique features of this protein in liver‐stage malaria infections.